Association of leptin and insulin resistance in PCOS: A case-controlled study - Bahia Namavar Jahromi; Mohammad Hassan Dabaghmanesh; Mohammad Ebrahim Parsanezhad; Faranak Fatehpoor (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Endocrine abnormalities related to polycystic ovary Syndrome (PCOS) are important problems. Objective: To compare serum leptin levels between infertile women with and without PCOS. To rank sensitivity of six indirect methods for detection of insulin resistance (IR) and to evaluate the association between leptin and IR in PCOS group. Materials and methods: This Case-controlled study performed on 189 infertile women referred to Shiraz Mother and Child Hospital during 2012-2015. Ninety-nine PCOS cases according to Rotterdam criteria were compared to 90 cases without PCOS. Serum leptin, body mass index (BMI), several hormones, and their correlation coefficients with leptin were compared. IR in PCOS women was measured by indirect methods, including fasting blood sugar (FBS), fasting insulin (FI), glucose/insulin, homeostatic model assessment of insulin resistance (HOMA-IR), quantitative insulin sensitivity check index (QUICKI), and MacAuley index. Association between IR and leptin was evaluated. Independent sample t-test and Pearson’s test were used. Results: Infertile women with PCOS had higher BMI (26.47±3.62 vs. 24.82±5.18 kg/m2) and serum leptin levels (41.79±187.89 vs. 19.38±12.57 ng/mL). Leptin showed significant association with weight and BMI in both groups (p<0.001) and to age in non-PCOS group. HOMA-IR showed the highest rate of IR followed by FI and QUICKI methods. The mean leptin levels had positive association with IR assessed by HOMA-IR (p<0.001), QUICKI (p<0.001), FI (p=.002), and FBS (p=0.02). Conclusion: BMI and IR have positive association with serum leptin in PCOS infertile women. HOMA-IR followed by FI and QUICKI is the most sensitive test for detection of IR.